Chromametric Techniques for IoT, real-time and reliable Food Freshness Measurement - Mohd Isnari, Mohamad Ariff (IRC, 2015)
Food Freshness is the main factor in determine the quality and safety of the food consumer to prevent them from having trouble such as food poisoning, stomach ache and etc. Nowadays, there are technologies that able to determine the level freshness of foods that depends on the changes of the colours which indicate the freshness level whether it is still edible to eat or not and also it is very subjective to people eyes. The goal of this paper is to design and develop chromatic algorithm based on RGB colour reading and correlation with pH values for real time determination of freshness level of fish. The results show that by developing the chromatic algorithm, will able to measure and analyse the level freshness of food and straight appear on the mobile application that has been developed. The mobile application itself is built by using Android studio platform and the level freshness of fish has been tested out to determine whether the fish is “FRESH, GOOD or SPOILED”